2020
DOI: 10.1038/s41598-020-72991-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-369-3p modulates inducible nitric oxide synthase and is involved in regulation of chronic inflammatory response

Abstract: Dendritic cells are the most important antigen-presenting cells that link the innate and acquired immune system. In our previous study, we identified that the upregulation of miR-369-3p suppresses the LPS-induced inflammatory response, reducing C/EBP-β, TNFα and IL-6 production. With the aim of gaining further insight into the biological function of miR-369-3p during acute inflammatory response, in the present study we identified novel gene targets of miR-369-3p and demonstrated the suppressive ability of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…Functionally, miR-369-3p overexpression inhibited the viability and motility of HCC cells ( 29 ). miR-369-3p expression was decreased in the inflamed intestinal regions obtained from patients with inflammatory bowel disease and the overexpression of miR-369-3p alleviated the inflammatory response in response to lipopolysaccharide ( 30 ). Consistent with the findings of previous studies, the expression levels of miR-369-3p were also decreased in TGF-β1-stimulated A549 cells and lung tissues from mice with BLM-induced fibrosis in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, miR-369-3p overexpression inhibited the viability and motility of HCC cells ( 29 ). miR-369-3p expression was decreased in the inflamed intestinal regions obtained from patients with inflammatory bowel disease and the overexpression of miR-369-3p alleviated the inflammatory response in response to lipopolysaccharide ( 30 ). Consistent with the findings of previous studies, the expression levels of miR-369-3p were also decreased in TGF-β1-stimulated A549 cells and lung tissues from mice with BLM-induced fibrosis in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA can regulate arginine metabolism by regulating the expression of key molecules in arginine metabolism pathway, such as ASS ( Bates et al, 2010 ; Tu et al, 2020 ), ARG1 ( Bates et al, 2010 ; Yoo et al, 2019 ), ARG2 ( Dunand-Sauthier et al, 2014 ; Jin et al, 2014 ; Kim et al, 2017 ; Wang Y. et al, 2017 ), CAT-1 ( Chang et al, 2004 ; Li Y. et al, 2018 ), ODC ( Jagannathan et al, 2015 ) and NOS ( Perske et al, 2010 ; Yan et al, 2011 ; Guo et al, 2012 ; Sun et al, 2012 ; Zhu et al, 2013 ; Li et al, 2014 , 2017 , Li H.T. et al, 2018 ; Fu et al, 2015 ; Jiang et al, 2015 ; Zhang et al, 2015 , 2020 ; Rasheed et al, 2016 ; Reilly et al, 2016 ; Muxel et al, 2017 , 2018 ; Wang C. et al, 2017 , Wang et al, 2019 ; Cui et al, 2020 ; Lin et al, 2020 ; Scalavino et al, 2020 ; Table 1 ). It has been found that multiple miRNAs could target the same enzyme or transporter protein, and the same molecule could also be regulated by multiple miRNAs.…”
Section: Mirnas and Long Non-coding Rnas In Arginine Metabolism And Crcmentioning
confidence: 99%
“…In keeping, miR-369 overexpression in these cells significantly decreased cytokine production (i.e. TNFα, IL6, IL-12, IL-1α, IL-1β) in response to LPS, and some anti-inflammatory cytokines, such as IL-10 and IL-1RA, were indirectly increased (76).…”
Section: Mir-369mentioning
confidence: 59%
“…miR-369 expression levels were found increased in serum samples and skin tissues deriving from psoriatic patients compared to healthy subjects and a positive correlation exists between skin miR-369 levels and PASI (64,75). miR-369 has emerged as a key regulator of inflammatory response in dendritic cells, since it decreases LPS-induced NO production, by targeting directly iNOS expression, and simultaneously inhibiting nuclear translocation of NF-kB (76). In keeping, miR-369 overexpression in these cells significantly decreased cytokine production (i.e.…”
Section: Mir-369mentioning
confidence: 99%
See 1 more Smart Citation